'ORPHEIOI HYMNOI' The generic contexts of the Orphic Hymns - Malamis, Daniel Scott Christos (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
Uncertainty surrounds the circumstances of Orphic Hymns' composition and their intended use. Their author has substituted their own identity for that of the mythological poet and there is no certain reference to the extant collection in any ancient source. They are, in this sense, decontextualised. This study aims to make a contribution to the ongoing debate concerning the hymns' composition, and the original function they might have served, through an analysis of their poetic and generic contexts. Following a detailed survey of scholarship on the hymns, I reflect first on the collection as a unified text, the constitutive parts of the individual hymns and the methods they employ for addressing, describing and praying to the gods. I then study a select group of stylistic features that the hymns prominently display: their use of phonic effects, including etymological figures, of antithesis and symmetrical patterning, and their extensive repetition of poetic formulae. In each case I discuss the deployment and significance of these poetic elements within the collection and consider the intertextual parallels suggested by their recurrence in Greek literary texts of all periods. This analysis reveals the hymns' engagement with an overlapping set of poetic traditions, including, most prominently, cultic hymns and oracles, gnomic poetry, the theological discourses of the Presocratic philosophers and, in particular, Orphic poetry in its many forms. It suggests moreover that the hymns engage deeply with the oral strategies of the earliest Greek poets, underscoring the conclusion reached by several recent scholars, that the extant collection is essentially performative and was intended to be recited and heard. I argue that the Orphic Hymns were not a unique text in their employment of the stylistic features studied here, but drew extensively upon earlier hymns composed in Orpheus' name. I further consider, in the light of this argument, the bearing this study has on the unresolved questions of the hymns' composition, whether by a single author or many, and the aims of the poet(s) who composed them.
Keywords: Orphic hymns; Poetics -- Early works to 1800; Hymns, Greek (Classical) -- History and criticism; Literary form